2021
DOI: 10.3390/nu13092982
|View full text |Cite
|
Sign up to set email alerts
|

Whole Grain Intakes Are Associated with Healthcare Cost Savings Following Reductions in Risk of Colorectal Cancer and Total Cancer Mortality in Australia: A Cost-of-Illness Model

Abstract: Whole grain consumption has been associated with the reduced risk of several chronic diseases with significant healthcare monetary burden, including cancer. Colorectal cancer (CRC) is one of the most common cancers globally, with the highest rates reported in Australia. Three servings of whole grains provide a 15% reduction in total cancer and 17% reduction in CRC risk; however, 70% of Australians fall short of this level of intake. The aim of this study was to assess the potential savings in healthcare costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…On a population level, swapping from refined grains to whole grains has the possibility of reducing the risk of chronic disease, in turn lowering the costs related to the burden of disease. A recent nutrition economics analysis found that a swap to whole grain from refined grain foods could provide significant healthcare cost savings for cardiovascular disease, type 2 diabetes, and cancer, particularly colorectal cancer, for the Australian population [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…On a population level, swapping from refined grains to whole grains has the possibility of reducing the risk of chronic disease, in turn lowering the costs related to the burden of disease. A recent nutrition economics analysis found that a swap to whole grain from refined grain foods could provide significant healthcare cost savings for cardiovascular disease, type 2 diabetes, and cancer, particularly colorectal cancer, for the Australian population [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…A three-step cost-of-illness analysis was developed on the basis of (1) estimates of current per capita [ 8 ] and a targeted level of legumes intake [ 6 ] among Australian adults (age 25+ y), (2) estimates of percent reductions in relative risk (95% CI) of CHD following legumes intake [ 14 ], and (3) recent data on annual costs related to CHD management within the Australian health care system [ 15 ]. To assess the uncertainty factor, a sensitivity analysis of four scenarios (very pessimistic, pessimistic, optimistic, and universal) was conducted, as modelled previously [ 12 , 13 ]. Input parameters are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the 2019 Global Burden of Disease data [ 8 ], in the first step of this analysis, the current estimated per capita legumes intake of 19.3 g/day for adults (age 25+ y) was compared to a targeted level of 50 g/day [ 6 ] and a calculation was built on estimates of proportions of Australian adults (age 25+ y) who are likely to increase their legumes intake by the gap amount of 30.7 g daily. As previously [ 12 , 13 ], here, the sensitivity analysis assumed very pessimistic, pessimistic, optimistic, and universal scenarios to represent 5%, 15%, 50%, and 100% (all) of prospective consumers who would reach the targeted daily level of legumes intake in the short term, short-to-medium-term, medium-to-long-term, and long-term, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations